f(n) = f(n-1) + 5 simply means
the next term or f(n), will have a value of
the one before it, or f(n-1), +5
so.. you're looking for the 4th term, that means f(4)
to get 4th term then, that will be the 3rd term plus 5,
whatever the 3rd term is
now... f(1) = -2, simply means, the term 1, or f(1), or first term, is -2
now to find a term value in an arithmetic sequence [tex]\bf f(n)=f(1)+(n-1)d\\\\
\begin{cases}
n=n^{th}\ term\to &4\\
f(1)=\textit{first term}\to &-2\\
d=
\begin{array}{llll}
\textit{common difference, or amount}\\
\textit{added to get the next term}
\end{array}\to &5
\end{cases}\\\\
-----------------------------\\\\
thus
\\\\
f(4)=f(1)+(4-1)5[/tex]
and I'm sure you know what f(1) is, so, just plug it in, to get f(4), or 4th term